2021
DOI: 10.1097/qad.0000000000002984
|View full text |Cite
|
Sign up to set email alerts
|

Associations between efavirenz concentrations, pharmacogenetics and neurocognitive performance in people living with HIV in Nigeria

Abstract: Objective: Efavirenz (EFV) use is associated with neuropsychiatric side effects, which may include poor neurocognitive performance. We evaluated single nucleotide polymorphisms in genes that contribute to EFV pharmacokinetics and examined them in association with EFV concentrations in plasma and hair, as well as neurocognitive performance. Design: Cross-sectional study in which adults with HIV receiving 600-mg EFV for at least 2 months were recruited and paired hair and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
5
2
Order By: Relevance
“…The CYP2B6 NPSs rates in Mozambique and others countries support the likelihood of influence of CYP2B6 SNPs on NVP/EFV metabolism and HIV-1RNA response among our study population [ 27 , 43 , 52 ]. Nevertheless, this hypothesis needs further investigations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The CYP2B6 NPSs rates in Mozambique and others countries support the likelihood of influence of CYP2B6 SNPs on NVP/EFV metabolism and HIV-1RNA response among our study population [ 27 , 43 , 52 ]. Nevertheless, this hypothesis needs further investigations.…”
Section: Discussionsupporting
confidence: 76%
“…A Mozambican study found the frequency of CYP2B6 SNPs (516T/785G of (34.7% and 42.6%) and 516T associated to high NVP toxicity among HIV/AIDS patients [ 48 , 49 ]. Likewise, carriers of CYP2B6 516G>T SNPs under NVP based ART had significantly higher NVP plasma concentration particularly the homozygotes CYP2B6 c.516T/T [ 41 – 44 , 50 ] Additionally, over threefold increase on EFV exposure in hair (long) and plasma (short) was reported among African American women [ 27 , 51 ] Nigerian patients [ 52 ] carrier of CYP2B6 516TT genotype. However, the role of CYP2B6 NPSs on low viral suppression still not clear [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CYP2B6, a higher risk of infection was observed in patients with a CYP2B6 metabolizer gene variant (rs2279343 GA). Although the G variant in rs2279343 has been previously correlated with efavirenz [34], methadone, bupropion, nicotine and others [35], no previous studies reported an association with immunosuppressant drugs. We do not know the reasons that could justify its association with infections.…”
Section: Discussionmentioning
confidence: 94%
“…For DBS, venous blood was collected from each participant and spotted on to Whatmann 903 protein saver cards (50 µl per spot). The procedure used has been previously reported [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of efavirenz concentrations in DBS was carried out at the Liverpool Bio-analytical Facility (BAF), Department of Molecular and Clinical Pharmacology, Institute of Translational Medicine, University of Liverpool using validated liquid chromatography tandem mass spectrometry (LC–MS/MS)-based methods [ 25 ]. Details of the laboratory methods used in this study have been reported previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%